PENERAPAN METODE COACHING DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR PADA SISWA KELAS VII SMP NEGERI SATAP NONOTBATAN TAHUN AJARAN 2023/2024 - Kolo, Anna Bertha; Yata Mones, Anselmus; Cornelis Usboko, Wilibrordus (Kanisius, 2025)
The research focus of this paper is the method taken to increase the learning independence of Class VII students at SATAP Nonotbatan State Middle School by using the coaching learning method. The steps of this method are coaching presence, active listening, powerful questions, giving feedback. The aims of this research are (1) to increase the learning independence of Class VII students at SATAP Nonotbatan State Middle School; (2) To determine the effectiveness of implementing the coaching method of learning on the material